Social-model aspects of disaster risk management in business processes - Tošović, Miloš (Sociološki pregled, 2024)
Modern business conditions, especially from a social point of view, require additional security of the work and business processes from the perspective of security and prevention of accompanying disasters and their consequences for society, companies and individuals. The main aim of this paper is to consider, through analytical analyses, the social-model aspects accompanying the socially important segment of security activities in the part of disaster risk assessment. It is the initial analytical setting that should enable a socially significant definition and application of risk management in various technical-technological and natural processes. The concluding consideration points to the direct social-security importance of appropriate model aspects in the comprehensive disaster risk management and their prevention in the social, working and living environment.
Keywords: social-model aspects; risk assessment; risk management; disasters; business processes